The Application of Jung's Personality Psychoanalysis in Attar and Rumi's Poetry Relying on the Two Categories of Joiner and Separation - Faezeh Payriz Zanjani; Mehdi Mahouzi; Seyedeh Mandana Hashemi Isfahan (Matn/Pizhūhī-i Adabī, 2024)
Despite the common thoughts of the poets who have stepped on the path of mysticism, each of them had a special style in depicting the ways and methods of conduct and their identification. In addition to the stylistic characteristics of a work, which play a decisive role in creating a different work, the spiritual and personality characteristics of the creator of the work also affect this matter. In this article, the personality of Attar and Rumi has been analyzed based on the theory of the famous psychologist, Gustav Jung, from the perspective of introversion and extroversion in the face of the two categories of joiner and separation. Considering the influence of the childhood environment, different incidents and events in the lives of the two poets, the difference in their views and narratives about the character of the lover, which is the main focus of romantic lyric poetry, and the moods related to it, as well as the poetic style and personality type of the two poets, it can be acknowledged that Attar has an emotional introverted character and has spoken more about Hejran (separation) than Vesal (joiner), and despite many descriptions about Hejran (separation), Rumi does not consider Vesal (joiner) to be out of reach and has an emotional extroverted personality.Keywords: Personality, Jung, Joiner, Separation, Attar, Rumi. IntroductionThe present research pays close attention to the two categories of separation and joiner in the sonnets of Attar and Rumi and has taken a special look at the personality of these two poets and examined their extroversion and introversion based on Jung's personality theory.This article examines the personality type of two poets by looking at the history and childhood of two poets and their poetic style, especially in dealing with concepts such as joiner and separation.Research Questions The present research will answer the following questions:How was the living environment and childhood of the two poets and what effect did it have on their personalities?What approach did Attar and Rumi have to the two categories of joiner and separation in their sonnets?From the point of view of psychology, what type of personality did these two poets have and what differences did this issue create in their narrative style?    Literature ReviewThere are many articles and research studies from the perspective of psychoanalysis in the field of Rumi's and Attar's poems, including the analysis of the archetype of the self in Attar's Mantiq al-Tair (Gholampour, 2015), the principle of Senkhiat and identification in psychology, with the thoughts of Attar and Rumi (Anzabinejad, 2014), a comparative study of the archetype of the veil in the opinions of Jung and its traces in the ghazals of Shams (Mohammadi, Esmailipour, 2013), the lover's anima in Attar's Ghazals based on Jung's archetypal criticism (Aqrani, 2017). The following article deals with the psycho-analysis of the personality of Attar and Rumi based on Jung's typological model. The subject of this research is an innovation based on the concepts of "joiner and separation" in order to know the personality type of two poets. MethodologyThe research method in this study is descriptive-analytical. First, the principles of Jung's psychology in the field of personality have been carefully studied; then, with a complete study of life, research on the content of behavior and the study of the two poets' sonnets based on psychological studies, the personality of Attar and Rumi has been examined. ConclusionIn his romantic sonnets, Attar talks more about separation and insists on the idea that the character of a lover is always in a state of fervency and is happy to make love and stay away from the beloved. On the other hand, although Rumi talks about burning and melting and separation, his tendency has been more towards happiness, hope, and joiner. Both poets, due to having a famous family, studied science and literature and had the good fortune to reach the final goal in this way; however, during Attar's childhood, very bitter events, especially the Ghoz attack, made his mind and soul suffer, and in the later years, according to the narrations, he was a reclusive man.Based on the clear evidence of Attar's lifestyle, i.e. his tendency towards poetry and mysticism, his isolation and lack of socializing with mystics and great men of his time, his avoidance of fame and the features of the lover's personality in the sonnets, including being sad, feeling disillusioned, and being happy with the separation, emphasis on disappointment in joiner, his character can be counted among the group of emotional introverts.On the other hand, apart from the bitter experience of migration, Rumi had more security during his childhood. Like his father, Bahavald, he became famous at a young age and enjoyed being in contact with great men and mystics and the people of the city. Based on pieces of evidence such as interest in acquiring knowledge and seeking fame, having many connections with scholars and students, states after his love experience - joy, mystic dance, music, and reciting poetry in the company of friends, also the personality characteristics of a lover in his Divan - the hope of being joined, special experiences of making love, which is a creative and unique thought - it can be said that Rumi had an emotional extroverted personality.